2023
DOI: 10.3389/fmicb.2022.1079764
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomic analyzes of human lung epithelial cells infected with wild-type SARS-CoV-2 and its variant with a 12-bp missing in the E gene

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a novel coronavirus that caused a global outbreak of coronavirus disease 2019 (COVID-19) pandemic. To elucidate the mechanism of SARS-CoV-2 replication and immunogenicity, we performed a comparative transcriptome profile of mRNA and long non-coding RNAs (lncRNAs) in human lung epithelial cells infected with the SARS-CoV-2 wild-type strain (8X) and the variant with a 12-bp deletion in the E gene (F8). In total, 3,966 differentially expressed ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
4
0
0
Order By: Relevance
“…Our results are in line with other transcriptome studies conducted in SARS-CoV-2infected Calu-3 cells, which showed responses associated with IFN I, II, or III signaling [13][14][15][16][17]; innate immunity, inflammation, and defense against virus [13,14]; TNF and IL-17 signaling [130], and signaling mediated by RIG-I/MDA5 [13,16]. In contrast, chemokine genes are generally up-regulated in infected Calu-3 cells [13][14][15]17,130], which were not found in our study (Supplementary File S1).…”
Section: Metabolic Transcriptional Model and Limitations Of The Studysupporting
confidence: 92%
See 3 more Smart Citations
“…Our results are in line with other transcriptome studies conducted in SARS-CoV-2infected Calu-3 cells, which showed responses associated with IFN I, II, or III signaling [13][14][15][16][17]; innate immunity, inflammation, and defense against virus [13,14]; TNF and IL-17 signaling [130], and signaling mediated by RIG-I/MDA5 [13,16]. In contrast, chemokine genes are generally up-regulated in infected Calu-3 cells [13][14][15]17,130], which were not found in our study (Supplementary File S1).…”
Section: Metabolic Transcriptional Model and Limitations Of The Studysupporting
confidence: 92%
“…Our results are in line with other transcriptome studies conducted in SARS-CoV-2infected Calu-3 cells, which showed responses associated with IFN I, II, or III signaling [13][14][15][16][17]; innate immunity, inflammation, and defense against virus [13,14]; TNF and IL-17 signaling [130], and signaling mediated by RIG-I/MDA5 [13,16]. In contrast, chemokine genes are generally up-regulated in infected Calu-3 cells [13][14][15]17,130], which were not found in our study (Supplementary File S1). This transcriptional picture with the predominance of INF and chemokine genes and the enrichment of pathways associated with interferon response and innate immunity was also described for Calu-3 cells infected with other respiratory viruses, such as Rhinovirus (RV), Influenza A (IAV), and Influenza B (IBV) [137].…”
Section: Metabolic Transcriptional Model and Limitations Of The Studysupporting
confidence: 92%
See 2 more Smart Citations